Gestational diabetes mellitus-associated changes in the breast milk metabolome alters the neonatal growth trajectory. Issue 6 (June 2021) - Wu, Yue; Yu, Jiaxiao; Liu, Xiyao; Wang, Wenling; Chen, Zhi; Qiao, Juan; Liu, Xiaohui; Jin, Huili; Li, Xin; Wen, Li; Tian, Jing; Saffery, Richard; et al.
Summary: Background: Gestational diabetes mellitus (GDM) is the most common metabolic disturbance during pregnancy and leads to an altered metabolic profile of human breast milk (HBM). The association between HBM metabolites and neonatal growth in GDM pregnancies has not been thoroughly investigated. Aims: The primary aim was to quantify differences in the HBM metabolome between normal and GDM pregnancies. The secondary aim was to identify metabolites associated with neonatal growth during the first year postpartum. Methods: In the present study, mothers intending to exclusively breastfeed (BF) and their newborns (mother–infant pairs) were recruited at delivery (n = 129 normal pregnancies and n = 98 GDM pregnancies). HBM samples (colostrum, transition milk, and mature milk) from mothers with normal pregnancies (n = 50) and GDM pregnancies (n = 50) were subjected to metabolomic profiling via liquid chromatography tandem mass spectrometry (LC-MS/MS). Receiver operating characteristic (ROC) analysis revealed the metabolomic fingerprints of GDM-associated mature HBM. Correlations between metabolites and neonatal body weight gain (BWG) were evaluated by Spearman correlation analysis. Results: In total, 620 metabolites were identified in each HBM sample; 253 compounds had the same variation patterns, whereas 38 compounds had significantly different pattern transitions between the GDM and normal groups. Moreover, 12, 49 and 28 metabolites exhibited significant differences in the 3 milk types between the 2 groups. Twenty-two metabolites were confirmed by ROC analysis as metabolomic fingerprints in the mature BM of GDM patients. Ten compounds were significantly negatively correlated with neonatal growth, and only 2 unsaturated lipids (eicosatrienoic acid (FA 20:3) and lysophosphatidylcholine (LysoPC) (22:6)) were positively correlated with neonatal BWG. Conclusions: GDM is associated with alterations in the HBM metabolome. Only a small subset of compounds are associated with neonatal body weight (BW). Trial registration: ChiCTR-ROC-17011508. Prospectively registered on 26 May 2017 (http://www.chictr.org.cn/listbycreater.aspx ).